The Alternative of Drainage Construction Technology Selection by Using Analytical Hierarchy Process Method - Hafnidar A Rani; Tamalkhani Syammaun; Aulina Adamy; Ari Fadillah (Elkawnie, 2021)
Abstract: The drainage channel is one of the complementary buildings on the road segment in requiring one of the technical requirements for road infrastructure. The road drainage channels in general are open channels using gravity to drain surface water or inundation to the channel. The distribution of flow in the drainage channel to this channel follows the contours of the highway so that the water will flow easily following gravity. The Several alternatives selection of drainage development technologies include elbow drainage, parallel, grid iron, natural and radial. The problem found that some factor considered in selection the right technology are the construction budget, construction period, material supply, and construction process affecting the selection process become complicated. The purpose of this study is to determine the dominant criteria required in considering the selection of drainage construction technology in Banda Aceh and to determine the proper alternative using Analytical Hierarchy Process (AHP) method. After distributing questionnaires to 16 respondents, the research found that the dominant criterion is the construction period as the score of 0.66. According to the respondents, the construction period become the most vital criteria since the assessment of criteria variable relate to the limitation in complete all drainage proposed. This study founds that the best alternative in selecting drainage construction technology is "parallel drainage" as the score is 4.96. Therefore, this study recommends the use of "parallel drainage" as a priority in the drainage construction Banda Aceh by considering construction budget, construction period, material supply and construction process.Abstrak: Saluran drainase merupakan salah satu bangunan pelengkap pada ruas jalan dalam memenuhi salah satu persyaratan teknis prasarana jalan. Pada umumnya saluran drainase jalan merupakan saluran terbuka yang menggunakan gaya gravitasi untuk mengalirkan air limbah ke outlet. Distribusi aliran di saluran drainase ke outlet ini mengikuti kontur jalan raya sehingga air limbah akan lebih mudah mengalir secara gravitasi. Beberapa alternatif pemilihan teknologi pembangunan drainase antara lain adalah drainase elbow, parallel, gridiron, natural dan radial. Persoalannya, beberapa faktor yang perlu dipertimbangkan dalam memilih teknologi yang tepat, biaya pembangunan, waktu konstruksi, ketersediaan material, dan proses pembangunan sehingga pilihan menjadi rumit. Tujuan dari penelitian ini adalah untuk menentukan kriteria dominan yang perlu diperhatikan dalam pemilihan teknologi pembangunan drainase di Kota Banda Aceh dan menentukan alternatif yang tepat melalui metode Analytical Hierarchy Process (AHP). Setelah menyebarkan kuesioner kepada 16 responden, penelitian menemukan bahwa kriteria yang dominan adalah waktu pengerjaan dengan bobot tertinggi (0,66). Menurut responden, waktu konstruksi merupakan kriteria yang paling penting karena keterbatasan dalam menyelesaikan seluruh usulan pembangunan drainase perlu dipertimbangkan. Studi ini menemukan bahwa alternatif terbaik dalam memilih teknologi pembangunan drainase adalah “drainase paralel” yang memperoleh nilai kinerja tertinggi sebesar 4,96. Oleh karena itu, penelitian ini merekomendasikan penggunaan “drainase paralel” sebagai prioritas dalam pembangunan drainase di Kota Banda Aceh dengan pertimbangan biaya, waktu konstruksi, ketersediaan material, dan proses pembangunan.